Civil wrongs and justice in private law - Miller, Paul B. 1977-; Oberdiek, John F. K. (Oxford University Press, 2020)
"Civil wrongs occupy a significant place in private law. They are particularly prominent in tort law, but equally have a place in contract law, property and intellectual property law, unjust enrichment, fiduciary law, and in equity more broadly. For example, some tort theorists maintain that tort law is best understood as a (or perhaps the) law of civil wrongs and some contract law theorists maintain that breach of contract is a civil wrong. Civil wrongs are also a preoccupation of leading general theories of private law, including corrective justice and civil recourse theories. According to these and other theories, the centrality of civil wrongs to civil liability shows that private law is fundamentally concerned with the expression and enforcement of norms of justice appropriate to interpersonal interaction and association. Others, sounding notes of caution or criticism, argue that a preoccupation with wrongs and remedies has meant neglect of other ways in which private law serves justice, and ways in which private law serves values other than justice. The present volume comprises original papers written by a wide variety of legal theorists and philosophers exploring the nature of civil wrongs, their place in private law, and their relationship to other forms of wrongdoing. It should be of broad interest to lawyers and legal theorists as well as moral and political theorists"--
Keywords: Unerlaubte Handlung; Privatrecht; Torts; Civil law